Comparison of Accuracy of Frameless Stereotactic System (Neuronavigation) Against Frame Based Stereotaxy in Deep Seated Lesion of Brain (Medical Forum Monthly, 2020)
Objective: The determination of accuracy of frameless stereotactic system against frame based stereotaxy in deep seated lesion of brain.Study Design: Randomized controlled trial study.Place and Duration of Study: This study was conducted at the Department of Neurosurgery, Nishtar Hospital Multan from June 2019 to June 2020.Materials and Methods: A total of 124 patients were included in the study after informed consent and eligible in accord to the inclusion and exclusion criteria. Total participants were 124 (randomized) and were divided into two randomized groups; frame-based stereotaxy group (FB) and stereotaxy group (SG) including 62 patients in each group. The angular deviation and target distance between actual and planned trajectory were the primary outcomes in this study. Independent samples were tested through 2-tailed t-tests for statistical testing. Mann-Whitney U test was performed for non-normally distributed data while for comparison of categorical variables Chi-square or Fisher tests were performed. P-value was 0.05 as a level off statistical significance. SPSS version 23 was used for statistical computations.Results: Trajectory length and distance were 42.32±10.38 mm and 2.43±1.02 mm in FB group, while 43.45±11.65 mm and 2.59±1.06 mm in VG group, and there was no statistically significant difference in these two parameters (p value 0.570 and 0.390, respectively). Trajectory deviation was 1.85±1.28 degree in FB group and 2.63±158 degree in VG group, and the difference was statistically significant (p=0.003). Table-2.Conclusion: Patients in which brain biopsy was done, the Varioguide system can be compared to the gold standard frame-based stereotaxy on the basis of means of trajectory accuracy, complications rate and diagnostic yield.